PENGARUH ATRAKSI, AMENITAS DAN AKSESBILITAS TERHADAP KEPUASAN WISATAWAN NUSANTARA DI PANTAI NYANG NYANG KABUPATEN BADUNG - Destiawan, Khalid Al Raif; Sofia Wijaya, Ni Made; Leli Kusuma Dewi, Luh Gede (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 2 (2023): Jurnal IPTA (December 2023), 2023)
This study aims to examine how attractions, amenities, and accessibility affect tourist satisfaction, providing recommendations to enhance the facilities and services offered at Nyang Nyang Beach. Employing a quantitative research approach, this study investigates the influence of attractions, amenities, and accessibility on tourist satisfaction at Nyang Nyang Beach. Data collection involved questionnaires, interviews, observations, literature review, and documentation. The sample size was determined using purposive sampling, resulting in a total sample of 100 participants, calculated following the formula by Hair et al. (1994). The data analysis encompassed instrument testing, testing of classical assumptions, multiple linear regression analysis, and hypothesis testing. SPSS 25 was employed for the data analysis. Based on the conducted analysis, the findings of this study indicate that attractions hold a significance value of 0.001, amenities have a significance value of 0.004, and accessibility has a significance value of 0.001. These results imply that each factor individually exerts a positive and significant influence on tourist satisfaction when visiting Nyang Nyang Beach. Furthermore, the calculated F value of 23.741 with a significance of 0.000 demonstrates that attractions, amenities, and accessibility collectively exert a positive and significant influence on tourist satisfaction.